Clinical Study of Analgesic and Anti-inflammatory Properties of Cannabis Derivatives in Patients with Temporomandibular Joint Pathology: Preliminary Study - Francisco Martínez Martínez; Marta Belén Cabo-Pastor; Félix De Carlos-Villafranca; Nuria García-Carrillo; Vidushi Jindal; José Luis Calvo-Guirado (Wolters Kluwer Medknow Publications, 2024)
We all know that the use of marijuana is a potent anti-inflammatory and analgesic and possible mechanisms of action and components that can help reduce the effects of pain in temporomandibular joint (TMJ) disorders. Our study aimed to analyze the anti-inflammatory and analgesic characteristics of cannabis derivatives in patients with temporomandibular pathology. Thirty-six patients were divided into three groups: one was treated with Cannabidiol (CBD) cream, the second was treated with CBD Vaper, and the third was treated with conventional anti-inflammatories such as Ibuprofen 600 mg. All patients underwent a dental computed tomography scan at the beginning and another at the end of treatment 28 days later. In addition to the study treatment of Cannabis and anti-inflammatories, all patients received physiotherapy treatment on day 0, day 14, day 21, and day 28 of the study. The study's results allow us to evaluate that using the CBD cream with physiotherapy results in a favorable pain reduction of 59%, CBD Vaper with physiotherapy has reduced pain by 35%, and the combined use of ibuprofen medication with physiotherapy has reduced pain by 45%. Therefore, using CBD and physiotherapy allows a biological reduction of pain and inflammation at TMJ. The most significant reduction in analgesia and pain occurred with CBD cream, followed by ibuprofen, which had less effect than CBD Vaper. We can control the pain of the TMJ with the use of CBD and treatment with the physiotherapist that allows us to maintain the dose and time of use of CBD both in cream and in Vaper; this improves the quality of life and returns the patient to cognitive relieving stress and anxiety.